Utilizing Deep Learning Models for Gene Selection from Microarray Expression Data - مسعودي عبد الرزاق (university of eloued جامعة الوادي, 2024)
عد اختيار الجينات من بيانات تعبير الجيني لمصفوفة الدقيقة مهمة حاسمة لتصنيف السرطان بدقة. تستكشف هذه الدراسة تطبيق نماذج التعلم العميق، بما في ذلك التشفير التلقائي و طرق أخرى لاختيار الميزات تعتمد على التعلم العميق، لتحديد أصغر مجموعة ممكنة من الجينات الذي يحافظ على الأداء التنبؤي العالي. يعد اختيار الجينات ذات الصلة أمًرا ضروريًا في معظم دراسات التعبير الجيني، بهدف تحديد الجينات الأكثر أهمية لمهام التصنيف المحددة. اختبار دقة التصنيف ، قمنا بتنفيذ العديد من نماذج التعلم الآلي والعميق مثل ( SVM , KNN ,MLP ,Forest Random) يتم تدريب هذه النماذج على جينات مختارة للتنبؤ بدقة التصنيف. يسلط هذا العمل الضوء على إمكانية الجمع بين اختيار الميزات القائمة على التعلم العميق ونماذج التصنيف المتقدمة لتحسين تشخيص السرطان واستراتيجيات العالج. تسهم هذه النتائج في مجال الطب الدقيق والبيولوجيا الحسابية من خلال إظهار فوائد الاستفادة من تقنيات التعلم الآلي الحديثة لتحليل البيانات الجينومية. Gene selection from microarray gene expression data is an essential task for accurate cancer classification. This study explores the application of deep learning models, including AutoEncoder, and other deep learning-based feature selection methods, to identify the smallest possible set of genes that maintain high predictive performance. Selection of relevant genes is essential in most gene expression studies, with the aim of identifying the most important genes for specific classification tasks. To test the classification accuracy, we implement several machine and deep learning models such as Nearest Neighbor (KNN), Support Vector Machine (SVM), Random Forest, and Multi-Layer Perceptrons (MLP). These models are trained on selected genes to predict classification accuracy. This study highlights the potential of combining deep learning-based feature selection with advanced classification models to improve cancer diagnosis and treatment strategies. These findings contribute to the field of precision medicine and computational biology by demonstrating the benefits of leveraging cutting-edge machine learning techniques to analyze genomic data.
memouer master infourmatique
Keywords: ختيار الجينات، بيانات تعبير مصفوفة الدقيقة، نماذج التعلم العميق، تصنيف السرطان، الطب الدقيق.; Gene selection; Microarray expression data; Deep learning models; Cancer classification; Precision medicine